Prevalence of Stroke and Stroke Risk Factors in Kanchanadit Hospital - ศิริยงค์, วิทวัส (Region 11 Medical Journal, 2018)
Introduction : Stroke is important problem in Thai public health. There are top cause of death and disability adjusted life year. Even survival patients carry over of disability. Ministry of public health force to developing stroke service plan for decrease mortality rate. Whereas increase access service with good quality,decrease complications, recurrent and disability of stroke. The goal of mortality rate of stroke less than 7% in 2017. Therefore Kanchanadit hospital realized in priority of stroke. Objective : To study the prevalence and risk factors of stroke patients in Kanchanadit hospital.Material and Method : Identified and analyzed as a cross-sectional analysis by collected data sampling of population since 23 June 2017 to 31 December 2017. Furthermore analyzed by descriptive statistic that was number, percent, mean, standard deviation and inferential statistic that was Chi-square test, ODDs ratio. Results : Prevalence of stroke in Kanchanadit hospital was 8.46%. One hundred and twenty one patients were diagnosed with stroke. Mean age ± S.D. of them were 68.82 ± 12.18 years-old. 73.6% are graduated at primary education. 82.6% had ischemic stroke. Hypertension and hyperlipidemia were significantlyrisk factors of stroke (p < 0.001 and p < 0.001, respectively). However, diabetes mellitus, atrial fibrillation and previous stroke were not associate (p=0.161, 0.145 and 0.315, respectively). Conclusion : Hypertension and hyperlipidemia were major risk factors of stroke in Kanchanadit hospital. So the healthcare providers should be aware and emphasize about this for prevention stroke.